Mechanical Competence and Bone Quality Develop During Skeletal Growth. (17th June 2019) - Zimmermann, Elizabeth A; Riedel, Christoph; Schmidt, Felix N; Stockhausen, Kilian E; Chushkin, Yuriy; Schaible, Eric; Gludovatz, Bernd; Vettorazzi, Eik; Zontone, Federico; Püschel, Klaus; Amling, Michael; Ritchie, Robert O; et al.
ABSTRACT: Bone fracture risk is influenced by bone quality, which encompasses bone's composition as well as its multiscale organization and architecture. Aging and disease deteriorate bone quality, leading to reduced mechanical properties and higher fracture incidence. Largely unexplored is how bone quality and mechanical competence progress during longitudinal bone growth. Human femoral cortical bone was acquired from fetal ( n  = 1), infantile ( n  = 3), and 2‐ to 14‐year‐old cases ( n  = 4) at the mid‐diaphysis. Bone quality was assessed in terms of bone structure, osteocyte characteristics, mineralization, and collagen orientation. The mechanical properties were investigated by measuring tensile deformation at multiple length scales via synchrotron X‐ray diffraction. We find dramatic differences in mechanical resistance with age. Specifically, cortical bone in 2‐ to 14‐year‐old cases exhibits a 160% greater stiffness and 83% higher strength than fetal/infantile cases. The higher mechanical resistance of the 2‐ to 14‐year‐old cases is associated with advantageous bone quality, specifically higher bone volume fraction, better micronscale organization (woven versus lamellar), and higher mean mineralization compared with fetal/infantile cases. Our study reveals that bone quality is superior after remodeling/modeling processes convert the primary woven bone structure to lamellar bone. In this cohort of female children, the microstructural differences at the femoral diaphysis were apparent between the 1‐ to 2‐year‐old cases. Indeed, the lamellar bone in 2‐ to 14‐year‐old cases had a superior structural organization (collagen and osteocyte characteristics) and composition for resisting deformation and fracture than fetal/infantile bone. Mechanistically, the changes in bone quality during longitudinal bone growth lead to higher fracture resistance because collagen fibrils are better aligned to resist tensile forces, while elevated mean mineralization reinforces the collagen scaffold. Thus, our results reveal inherent weaknesses of the fetal/infantile skeleton signifying its inferior bone quality. These results have implications for pediatric fracture risk, as bone produced at ossification centers during children's longitudinal bone growth could display similarly weak points. © 2019 American Society for Bone and Mineral Research.